1989
DOI: 10.1897/1552-8618(1989)8[915:ciopcb]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Inhibition of Peripheral Cholinesterases by Neurotoxins From the Freshwater Cyanobacterium Anabaena Flos-Aquae: Studies of Ducks, Swine, Mice and a Steer

Abstract: Freshwater algal blooms associated with outbreaks of sudden death in ducks and swine were examined for cholinesterase (ChE)‐inhibiting toxins as the possible cause of death. In both investigations, Anabaena flos‐aquae was identified as the predominant alga in the bloom material. In both cases, assays on tissues from mice dosed intraperitoneally with algal extracts revealed inhibition of ChE in whole blood, plasma, diaphragm and lung, but not in brain. With algae from the field case involving ducks, toxicosis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 4 publications
(15 reference statements)
2
27
0
2
Order By: Relevance
“…Anatoxin-a(s) is a acethylcholinesterase inhibitor with a mechanism similar to that of the organophosphorus insecticides. However, anatoxin-a(s) acts only in the periphery and thus brain and retinal cholinesterase activities remain normal even in lethally poisoned animals [21]. The neurological effects in mice given acute doses are muscle weakness, respiratory distress (dyspnea) and convulsions (effect on seizure threshold) preceding death.…”
Section: Anatoxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anatoxin-a(s) is a acethylcholinesterase inhibitor with a mechanism similar to that of the organophosphorus insecticides. However, anatoxin-a(s) acts only in the periphery and thus brain and retinal cholinesterase activities remain normal even in lethally poisoned animals [21]. The neurological effects in mice given acute doses are muscle weakness, respiratory distress (dyspnea) and convulsions (effect on seizure threshold) preceding death.…”
Section: Anatoxinsmentioning
confidence: 99%
“…Anatoxin-a(s) also produced by A. flos-aquae was responsible for the death of dogs, pigs and ducks in USA [71] and waterfowl in Canada [98]. However, Cook et al [21] suggested that cattle could be resistant to ingestion of anatoxin-a(s). In South America, M. aeruginosa (producing microcystins) has been implicated in the sudden death of 72 cows in Argentina [87].…”
Section: Cyanobacterial Poisoning Of Terrestrial Vertebratesmentioning
confidence: 99%
“…Based on the duration of anatoxin-a(s) induced clinical signs and ChE inhibition in mice, anatoxin-a(s) appears to be an in vivo irreversible inhibitor of ChEs (Cook et al, 1991). In another study, Cook et al (1989c) demonstrated that anatoxin-a(s) inhibits AChE activity only in the periphery, while the OP or carbamate can inhibit AChE in the brain and retina as well.…”
Section: Anticholinesterase Propertiesmentioning
confidence: 98%
“…In Brazil, cyanotoxins have been reported in several studies: microcystins (Azevedo et al 1994;Matthiensen et al 2000;Minillo et al 2000;Vieira et al 2005;SoteroSantos et al 2008;Ferrão-Filho et al 2009), cylindrospermopsin (Carmichael et al 2001), saxitoxins (Lagos et al 1999Yunes et al 2003;Molica et al 2005;Ferrão-Filho et al 2009), and anatoxin-a(s) (Monserrat et al 2001;Yunes et al 2003;Molica et al 2005). However, anatoxin-a has never been found at detectable levels (Molica et al 2005;Colvara 2005). The genus Anabaena includes common filamentous bloom-forming cyanobacteria of world-wide distribution, and some species are able to produce toxins, such as hepatotoxins (microcystins) and neurotoxins [anatoxin-a, anatoxin-a(s), and saxitoxins] (Codd et al 1997, Sotero-Santos et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of anatoxin-a(s) has been reported from the United States, Canada, and Denmark (USEPA 2001). This toxin is mainly related to the deaths of dogs, birds, ducks, and other domestic animals caused by blooms of Anabaena lemmermannii ) and A. flos-aquae (Mahmood et al 1988;Cook et al 1989). Toxic blooms of A. crassa (Lemmermann) Komárková-Legnerová are common in reservoirs of the city of Caxias do Sul (Frizzo et al 2004).…”
Section: Introductionmentioning
confidence: 99%